Variable speed drives system integration - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The VARIABLE SPEED DRIVES: System Integration training program, or unit, is designed to familiarize trainees with several common ways in which variable speed drives and automated systems are linked together. After completing this program, the trainees should be able to describe how variable speed drives are integrated into distributed control systems and programmable control systems. They should also be able to describe the operation of tachometers, encoders, and resolvers, and explain how to install field devices for variable speed drives.
Keywords: Variable speed drives; Electric driving